Preoperative C‐reactive protein to prealbumin ratio is independently associated with prognosis in patients with resectable colorectal cancer. Issue 8 (17th February 2022) - Huang, Zhe; Cai, Pengzhu; Zhao, Yumei; Niu, Dongdong; Xu, Feipeng; Lai, Yousheng; Pang, Jinglin; Qi, Jiaming; Wu, Jiayuan
Abstract: Background: Increasing attention has been drawn the prognostic value of inflammatory indices for colorectal cancer (CRC). However, the prognostic value of the preoperative C‐reactive protein to prealbumin ratio (CPAR) in CRC remains unclear. Methods: A retrospective study was conducted with 794 patients who had CRC and underwent radical surgical resection. The predictive performance of the inflammatory indices was analyzed and compared using the area under the time‐dependent receiver operating characteristic curve. A competing risk regression model and Cox proportional hazard model were used to analyze the effects of CPAR on disease‐free survival (DFS) and overall survival (OS), respectively. Results: Patients with high CPAR (>7.25) had poor survival outcome. The CPAR had the best predictive performance among all inflammatory indices, and was significantly associated with several characteristics of tumor invasion, including histological grade, tumor stage, and tumor size. Multivariate analysis showed that high CPAR was independently associated with poor DFS (subdistribution hazard ratio = 2.28, 95% confidence interval [CI]: 1.74–2.82) and OS (hazard ratio = 1.78, 95% CI: 1.60–1.96). Conclusion: Preoperative CPAR assessment could serve as an effective and reliable tool for prognostic prediction in patients with resectable CRC.